Ostrov . Ostrov . Island . Остров - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Japanese poaching on Russia's eastern borders; plans for an oil processing factory. Featured in the program: Chernomyrdin, Viktor Stepanovich (Prime Minister of the Russian Federation) Проблема японского браконьерства на восточных границах России; проект нефтеперерабатывающего завода. В программе участвуют: Черномырдин, Виктор Степанович (Председатель правительства Российской Федерации)